Psychometric testing of the training needs for advance care planning scale for clinicians and nurses - Chunju He; Tiaoxia Dong; Jin Tan; Liu Yang; Yeyin Qiu; Jianghui Zhang; Yi Huang; Aiting Zhou; Xianlin Wang; Yuan Huang; Minglan Zhu; Simon Ching LAM; et al. (BMC Nursing, 2024)
Abstract Background Studies have shown that Chinese Clinicians and nurses have positive attitudes toward ACP, but no local tools exist to assess their need for ACP knowledge and skills training. resulting in their inability to initiate ACP conversations as well as poor end-of-life care for patients. Therefore, this study aims to assess the needs of Chinese Clinicians and nurses for ACP knowledge and skills training and assess the validity and reliability of a questionnaire on the Training Needs for Advance Care Planning (TNACP) scale. Methods From October to November 2021, 170 clinicians and nurses were pre-surveyed using a preliminary draft of the questionnaire. The responses were screened using item analysis, Cronbach’s alpha coefficient, and the intraclass correlation coefficient (ICC) to describe the internal consistency and stability of the questionnaire. The Content validity index (CVI), Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) were used to test the validity of the questionnaire. Results After independent samples t-test analysis, Except for the entry “A2”, the critical ratio between the two groups of the remaining 23 items was statistically significant (p < 0.05). Based on the above screening methods, the “A2” item was deleted, and the final number of questionnaire items was 23. The I-CVI was 0.79–1.00, and the S-CVI/Ave was 0.90. Three common factors were extracted—the cumulative contribution rate was 69.969%, and the factor loading of all items was 0.506–0.843 (all > 0.40). The results of confirmatory factor analysis showed that the Training Needs for Advance Care Planning (TNACP) scale model fit well(X2/df = 2.504, RMSEA = 0.092, GFI = 0.809, AGFI = 0.745, CFI = 0.931, IFI = 0.932, TLI = 0.916); the Cronbach’s α = 0.888 for the total questionnaire, and the three dimensions of Cronbach’s α were 0.729 to 0.959; and the ICC for the overall scores between the test-retest evaluations was 0.884 (p < 0.001). Conclusions The TNACP scale has good reliability and validity and can be used to assess Chinese Clinicians and nurses’ training needs for implementing ACP.